Lean Six Sigma Approach for Wait Time Analysis in Radiology Services at Krakatau Medika Hospital - Nur Fadhilah, Alifah; Ayubi, Dian (Devotion : Journal of Research and Community Service, 2023)
Krakatau Medika Hospital (RSKM), an integral part of Indonesia Healthcare Corporation (IHC), grapples with challenges in radiology services and wait time standards. Amidst the surge in healthcare facilities, IHC, overseen by PT Pertamina Bina Medika, strategically plans Lean Six Sigma implementation to enhance radiology quality, efficiency, and customer satisfaction. Non-Communicable Diseases (NCDs) complexities.  The research methodology adopts a qualitative approach, incorporating process flow observations, document reviews, and in-depth interviews at the Radiology Installation of Krakatau Medika Hospital. Data collection involves direct observations, in-depth interviews, and research instruments with various stakeholders. The study, encompassing January to July 2023, reveals RSKM's radiology indicators falling short, with excessive wait times jeopardizing service effectiveness. The Lean Six Sigma approach, utilizing the DMAIC methodology, aims to eliminate waste, improve processes, and enhance organizational performance. Findings emphasize the urgency for improvements, with Lean Six Sigma anticipated to play a pivotal role in reducing wait times and overall performance enhancement. Ethical considerations guide the research, ensuring informed consent and confidentiality. Collaborative efforts with RSKM management are vital for sustained positive outcomes. The study underscores Lean Six Sigma's potential benefits, emphasizing ethical healthcare research principles